Global trends and challenges in bilingual teacher education: A systematic review across sociocultural context - Abdulrahman, Tryanti R.; Akber, Talha; Werghemmi, Marwa; Ashraf, Iman; Azahra, Mona; Budi P.W.D, Ni Putu Eka; Ul Haq, Qazi Muhammad Zulqurnain (International Journal of Education and Learning, 2025)
As global interconnectedness increases, the demand for high-quality bilingual education and by extension, well-prepared bilingual educators, has grown significantly. This systematic review investigates global trends and challenges in bilingual teacher education across diverse sociocultural contexts. A total of 68 peer-reviewed studies published between 2005 and 2022 were analyzed using SaldaÃ±aâ€™s coding method, with data sourced from six major databases and selected through PRISMA guidelines. Thematic analysis revealed six core areas: global research trends in teacher preparation, evolving teacher competencies, identity formation and intercultural competence, pedagogical models, language policy, and implementation challenges. Findings show that successful bilingual teacher preparation programs are supported by culturally responsive pedagogy, robust policy alignment, and sustained professional development. However, disparities persist due to inadequate training infrastructure, restrictive policies, and lack of localized resources especially in underrepresented regions. The review underscores the need for teacher education models that are context-sensitive, equity-driven, and globally informed. It calls for expanded research in the Global South, integrative policy frameworks, and institutional commitment to build a resilient, inclusive bilingual teaching workforce.